Sub-Rhodian Amphorae in the Roman Province of Thrace. Is the form a Trademark for the Content? - Borislavova, Nadezhda (Rei Cretariae Romanae Fautorum Acta, 2022)
The aim of the research is to discuss the issue of derivative forms of the Rhodian type amphorae and the possible connection between the content and the shape of the vessels. The problem of reproduction of the Rhodian form in different regions of the eastern Roman provinces is discussed in the context of the finds from the Roman province of Thrace. The different subtypes were distinguished for their regional morphological features. Some of them are related to a probable region of origin. Almost all of the derivative forms were presented in Thrace but some of them predominate. Their wide distribution, extending over the markets of the urban centres and the rural areas, is an evidence for the traditional economic relations between Thrace, Aegean Islands and Western Asia Minor.